Edward Arnold : 100 years of publishing - Bennett, Bryan (Edward Arnold, 1990)
Edward Arnold: 100 Years of Publishing presents a comprehensive examination of the life of Edward Augustus Arnold. It discusses the developments that his publishing company achieved. It addresses the remarkable contributions of the person in the publishing industry.